Kontribusi Dana Desa terhadap Pembangunan dan Pemberdayaan Masyarakat di Kebumen dan Pekalongan - Arif Sofianto (Research and Development Agency Ministry of Home Affairs, 2017)
Number 6 of 2014 aims to optimize development and community empowerment in villages. One of the main important change is the allocation of funds from the state budget in a village fund scheme. This research aims to study the contribution of the village fund for rural development and community empowerment. Conducted in Kebumen and Pekalongan regency, this research employs descriptive qualitative type of research. Informants were determined purposively by considering village typology representation. Data collection methods in this study consist of interviews, questionnaires, focus group discussions, and observation. The method of data analysis in this research is conducted with interactive model approach in the form of data reduction, data display, and data verification. The conclusion of this study is that the implementation of village funds contributed to the society by increasing the accessibility of rural communities and community participation in development.